How to cheat at Windows system administration using command line scripts - Bhardwaj, Pawan K.; Andreou, Kimon; Barber, Brian; Kleiman, Dave.; Satyanarayana, Mahesh; Safari eBooks (Rockland, [Mass.] : Syngress, 2006)
The book is divided into five sections. The first section covers the basics of command line scripts and batch files including, usage of filters, conditional processing and command redirection. Readers will learn to create and schedule tasks to automating administration jobs from the Task Scheduler and from the command prompt. Part two discusses basic Windows administration including disk check, disk defragmentation, converting basic disks to dynamic, and file system commands as well as administering partitions and volumes. Part three focuses on scripting Active Directory including administering user and group accounts, and administering computers and domains. Part four moves on to Windows networking where the reader will learn to troubleshooting command-line tools, manage network printers, manage services for DHCP, DNS, WINS services as well as manage and monitor security including Microsoft Baseline Security Analyzer and certificate services. In the final part of the book, readers learn to manage Windows systems including starting and stopping services, configuring service startup types, managing event log files, setting log filters, configuring system monitor, starting a performance log, setting objects, and configuring performance alerts.
Includes index.
Electronic reproduction.
Keywords: Computer networks -- Security measures; Firewalls (Computer security); Operations systems (Computer); Microsoft Windows; Computer security; Electronic books